2021
DOI: 10.32920/ryerson.14639880.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrimination experienced by landed immigrants in Canada

Abstract: Immigrants land in Canada with great hopes and multiple dreams, but the General Social Survey 2009 shows that one-fifth of them face discrimination in various situations once they have arrived. Ethnicity, race, language, and religion are the major grounds of discrimination. In this paper, the experiences of discrimination of landed immigrants are compared with those of non-immigrants. A logistic regression analysis is used on GSS data to predict the probability of facing discrimination based on the socio-econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Although Canada has one of the largest foreign-born populations of all nations, not all immigrant groups are accepted by the majority host (Nangia, 2013). Some immigrants face higher levels of exclusion because they have certain attributes that are considered less desirable among host citizens.…”
Section: Canadian Immigration and Acculturation Orientationsmentioning
confidence: 99%
“…Although Canada has one of the largest foreign-born populations of all nations, not all immigrant groups are accepted by the majority host (Nangia, 2013). Some immigrants face higher levels of exclusion because they have certain attributes that are considered less desirable among host citizens.…”
Section: Canadian Immigration and Acculturation Orientationsmentioning
confidence: 99%
“…There is a relatively large body of research that has investigated the prevalence and the bases of discrimination experiences of immigrants, racialized individuals, and Indigenous peoples in Canada (e.g., Environics Institute for Survey Research 2019, 2021; Godley 2018; Ibrahim 2018; McCaskill 2012; Nangia 2013; Kong et al. 2020; Statistics Canada 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020; Statistics Canada 2020). For example, Nangia (2013) analyzed data from the 2009 General Social Survey (GSS) and found that 13 percent of immigrants had multiple experiences of discrimination within a 5‐year period compared to less than 7 percent of non‐immigrants. The most common forms of discrimination faced by immigrants were based on ethnicity or culture (13 percent), followed by race or color (11 percent).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many barriers will make this process challenging, among which discrimination is at the forefront. For example, immigrants in Canada have reported feeling discriminated against as they attempt to receive private and public services, secure employment and progress in their careers, engage in educational settings, find housing, and be involved in community organizations (Dion, 2001; Dion & Kawakami, 1996; Nangia, 2013). The consequences of discrimination on members of minority cultures has been well established (e.g., Branscombe, Schmitt, & Harvey, 1999; Noh & Kaspar, 2003; Williams, Neighbors, & Jackson, 2003).…”
mentioning
confidence: 99%